PEMISAHAN SENYAWA-SENYAWA YANG BERSIFAT SITOTOKSIK TERHADAP SEL MURIN LEUKEMIA P388 DARI EKSTRAK METANOL KULIT BATANG DIPTEROCARPUS CONFERTUS SLOOT (DIPTEROCARPACEAE) - . Muhtadi; Peni Indrayudha (Biomedika, 2013)
Six compounds, KP-1 up to KP-6 were isolated from the methanol extract of the tree bark of Dipterocarpus confertus Sloot (Dipterocarpaceae). The cytotoxic activities of these compounds were evaluated against murine leukemia P388 cells. Result of these examination indicated that KP-2 compound and KP-1 were very active with each IC 50 value of these compounds were 2.25 and 5.1 μg/mL, respectively. While the others were not active against murine leukemia P388 cells.Keywords: Dipterocarpaceae, Dipterocarpus confertus Sloot, isolated compounds, cytotoxic, and leukemia P-388 cell